K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

21 tháng 9 2017

https://hoc24.vn/hoi-dap/ti-le-thuc.4497/

1 tháng 10 2017

\(\dfrac{-12}{1,6}=\dfrac{55}{-7\dfrac{1}{3}}\)

\(\Rightarrow\dfrac{-12}{-7\dfrac{1}{3}}=\dfrac{55}{1,6};\dfrac{-12}{55}=\dfrac{-7\dfrac{1}{3}}{1,6};\dfrac{1,6}{55}=\dfrac{-7\dfrac{1}{3}}{-12};\dfrac{1,6}{-7\dfrac{1}{3}}=\dfrac{55}{-12}\)

\(\dfrac{-12}{-7\dfrac{1}{3}}=\dfrac{1.6}{55};\dfrac{1.6}{-12}=\dfrac{-7\dfrac{1}{3}}{55};\dfrac{-7\dfrac{1}{3}}{-12}=\dfrac{55}{1.6}\)

15 tháng 9 2017

\(Từ\) \(\dfrac{-1,2}{1,6}=\dfrac{55}{-7\dfrac{1}{3}}\Rightarrow\) \(\dfrac{1,6}{-1,2}=\dfrac{-7\dfrac{1}{3}}{55}\)

\(\Rightarrow\dfrac{-7\dfrac{1}{3}}{55}=\dfrac{1,6}{-1,2}\)

\(\Rightarrow\dfrac{55}{-7\dfrac{1}{3}}=\dfrac{-1,2}{1,6}\)

26 tháng 9 2017

cảm ơn

N
18 tháng 9 2017

1)

a) \(1\dfrac{5}{6}=\dfrac{-x}{5}\)

\(\Rightarrow\dfrac{11}{6}=\dfrac{-x}{5}\)

\(\Rightarrow-x=\dfrac{5.11}{6}=\dfrac{55}{6}\)

\(\Rightarrow x=-\dfrac{55}{6}\)

b) 4,25 : 8 = -3,5 : x

\(\dfrac{4,25}{8}=\dfrac{-3,5}{x}\)

\(x=\dfrac{-3,5.8}{4,25}\)

\(x=\dfrac{-28}{4,25}\)

2.

\(-\dfrac{12}{1,6}=\dfrac{55}{-7\dfrac{1}{3}}\)

\(\Rightarrow-\dfrac{12}{1,6}=\dfrac{55}{-\dfrac{22}{3}}\)

Ta có thể lặp đc các tỉ lệ thức sau:

\(-\dfrac{12}{1,6}=\dfrac{55}{-\dfrac{22}{3}}\)

\(\dfrac{-\dfrac{22}{3}}{1,6}=\dfrac{55}{-12}\)

\(-\dfrac{12}{55}=\dfrac{1,6}{-\dfrac{22}{3}}\)

\(\dfrac{1,6}{-12}=\dfrac{-\dfrac{22}{3}}{55}\)

1 tháng 10 2017

Tỉ lệ thức

15 tháng 9 2019

thanks

25 tháng 3 2022

\(\dfrac{1}{5}+\dfrac{2}{11}< \dfrac{x}{55}< \dfrac{2}{5}+\dfrac{1}{5}\)

\(\dfrac{11+10}{55}< \dfrac{x}{55}< \dfrac{3}{5}\)

\(\dfrac{21}{55}< \dfrac{x}{55}< \dfrac{33}{55}\)

Vậy \(x\in\left\{22;23;24;...\right\}\)

 

25 tháng 3 2022

\(\dfrac{????????}{????????????}\)

a: \(=\dfrac{-7}{8}\left(\dfrac{3}{5}+\dfrac{2}{5}\right)+3+\dfrac{7}{8}=\dfrac{-7}{8}+\dfrac{7}{8}+3=3\)

b: \(=-\dfrac{8}{5}:\dfrac{5}{3}=-\dfrac{24}{25}\)

c: \(=\dfrac{6}{7}+\dfrac{1}{8}-\dfrac{3}{4}=\dfrac{6}{7}+\dfrac{1}{8}-\dfrac{6}{8}=\dfrac{6}{7}-\dfrac{5}{8}=\dfrac{48}{56}-\dfrac{35}{56}=\dfrac{13}{56}\)